Pengaruh Produk, Harga dan Promosi Terhadap Keputusan Pembelian Air Minum Dalam Kemasan (AMDK) Merek Le Minerale di Samarinda - Firdayanti, Devi Indah (EKONOMIA, 2020)
The purpose of Â this research is to determine the product's influence, price, and promotion to the purchase decision of bottled drinking water (AMDK) brand Le Minerale in Samarinda. The theories used in this research are products, prices, promotions and purchasing decisions.This research was conducted in Samarinda. Samples taken as many as 100 respondents with Non Probability Sampling method with sampling technique using sample Purposive. Data collection with the spread of questionnaires using a likert scale to measure each indicator. Analytical tools in research using multiple linear regression analyses using SPSS V20 program.The results of this study showed that the product has a positive and significant effect on the purchase decision of bottled drinking water (AMDK) brand Le Minerale in Samarinda, the price is positive and not significant to the purchase decision of bottled drinking water (AMDK) brand Le Minerale in Samarinda, the promotion of positive and significant effect on the purchase decision of bottled drinking water (AMDK) brand Le Minerale in Samarinda and the products, prices and promotions jointly effect significantly On the decision of the purchase of bottled drinking water (AMDK) brand Le Minerale in Samarinda.